(untitled) (Revista Contexto & Educação, 2020)
This article analyzes some strategies of resistance produced in a project-experience promoting the discussions of gender and sexuality in the school space. We articulate questions on the mechanisms of power and strategies of resistance of three teachers who participated in the project. The theoretical framework used in our analysis is inspired by Foucaultian studies, on gender and sexuality. Data was collected in interviews and discussion groups. We were able to identify the strategies promoted by the teachers, such as: working with the theme by using terms and subjects of greater general acceptance; incorporate the theme into the content of existing courses; maintain a dialogue with the families and the community about the development of the project; advocate for inclusion of the theme in the documents that provide educational guidelines, among others, seeking to maintain the articulation and the discussions on the theme in their classrooms. Finally, it is fundamental to have proposals that promote the resistance and allow the problematization and the debate on gender and sexuality issues to enable a less discriminatory and sexist school space.